PENGARUH LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Muhammadinah, Muhammadinah (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2021)
This research aims to determine the effect of liquidity on dividend policy with profitability as an intervening variable. The population in this study is all general insurance companies of sharia units registered with the Financial Services Authority (OJK) in 2014-2018 which numbered 25 general insurance companies sharia units. Sampling technique using purposive sampling so that a sample of 19 general insurance companies shari'ah unit with the annual financial report for 5 years (2014 - 2018) so that the amount of data used in this study as much as 19 * 5 = 95 research data. The analysis technique used is path analysis using a t-test, where mediation testing is carried out with a procedure developed by Sobel (1982) and known as Sobel Test. The results showed that 1) liquidity variables directly affect and are insignificant to variable profitability, 2) liquidity variables directly affect and are significant to dividend policy variables, 3) variable profitability directly affects and is significant to dividend policy variables and 4) variable profitability is unable to mediate the effect of liquidity variables on dividend policy variables.